FORMULATION AND EVALUATION OF ACECLOFENAC MUCOADHESIVE MICROSPHERES FOR ORAL CONTROLLED DRUG DELIVERY - SAROJA SP; PREETHI SUDHEER (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Drug delivery is a broad field of research on the development of novel materials or carrier systems for effective therapeutic delivery of drugs. The main purpose of delivering the drugs to mucosal membrane is lengthening of the residence time at site of drug delivery, followed by sustained release of the drug after the deposition. Aceclofenac is a non-steroidal anti-inflammatory drug that has a half-life of 4 h. The frequent administration of the drug irritates the gastric mucosa when it is given in conventional dosage forms. Method: Hence in this study, a mucoadhesive microsphere of biopolymer chitosan was formulated with an aim to enhance the efficacy of the drug. The microsphere of aceclofenac was prepared by o/w/o emulsification cross linking method. Results: Various ratios of drug: polymer were studied, and it was found that microspheres with 1:4 ratio was the superior in terms drug content of 87.23±0.56%.and entrapment efficiency of 85.8±0.16 %.The in vitro drug release profiles indicated a maximum drug release of 89.55± 0.62 % in 12 h. The extent of mucoadhesion and ex- vivo permeation of the drug was studied using porcine intestinal mucosal sample. The microspheres were retained on the intestinal mucosa up to 12 h. The surface of the selected microsphere formulation was observed to be uneven during surface electron microscopic studies. Infrared spectroscopy and differential scanning calorimetry studies indicated that there was no major interaction between the drug and the polymer used. Conclusion: Therefore, the studies demonstrate that mucoadhesive microspheres could be an appropriate dosage to improve the gastric retention and efficacy of aceclofenac.